ANALISIS STRATEGI PENGUATAN KARAKTER DISIPLIN MELALUI PEMBIASAAN DI SEKOLAH DASAR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore methods for improving discipline through habit formation in elementary schools. This research is based on the importance of character education as a vital element in the national education framework, especially in fostering student discipline from an early age. This study used a literature review method by analyzing various materials, including books, academic articles, and relevant scientific studies. The results showed that reliable habit formation techniques, such as punctuality, fulfilling cleanliness responsibilities, praying before and after class, and obeying school rules, effectively foster discipline in students. Furthermore, the influence of teachers as role models, the use of positive reinforcement, and collaboration between schools and families are crucial factors that strengthen the implementation of these methods. With a structured and sustainable strategy, habit formation can instill a deep disciplined mindset in students and create a supportive, harmonious learning environment oriented towards sustainable and responsible character development.